Utilizing Aqueous Extracted Fraction Of Mangifera Indica For The Green Synthesis Of Zinc Oxide Nanoparticles - Mradul Mishra; Surya Prakash Gupta (Revista Electronica de Veterinaria, 2024)
The present study was commenced with an objective to produce zinc oxide nanoparticles aided with Mangifera indica leaf extract and study the antibacterial activity of the nanoparticles. The leaves of Mangifera indica were extracted using deionized water using cold maceration method. The zinc oxide nanoparticles were produced utilizing the plant extract with zinc nitrate in alkaline condition. The synthesized ZNPs were characterized using spectrometry, XRD, particle size and SEM. The lowest particles size was obtained with 30% extract concentration in relation to the zinc nitrate solution. The particle size was between 44.2 nm to 27.4 nm. The ZNPs were found to be spherical structures with smooth surface. The reduction and thermal decomposition were carried out to conclude a reduction in particles size with an initial increase in concentration of the extract but after increasing the concentration to higher than 30% the particle size remained unaffected. The UV absorption spectra revealed broad absorption band at around 367 nm, characteristic of zinc oxide. The ZNP displayed antibacterial action in gram positive and gram-negative bacteria. It could be concluded from the results that the aqueous extract of Mangifera indica was effective for biosynthesizing zinc oxide nanoparticles with good antibacterial activity.